Serum level of N-terminal propeptide of type I procollagen in people of various ages and gender - V.V. Povoroznyuk; N.V. Zaverukha; T.Y. Solonenko (Bolʹ, Sustavy, Pozvonočnik, 2020)
Background. The purpose of the study is to determine the serum level of N-terminal propeptide of type I procollagen (PINP) in healthy men and women of various ages. Materials and methods. The study included 1,568 individuals (1,422 females and 146 males, aged 20-89 years (mean age 60.36 ± 13.68 yrs). All patients were divided into 7 groups, by decades and according to the gerontological age classification: young age – 20–44 yrs, middle age 45–59 yrs, elderly 60–74 yrs, and old 75-89 yrs. During the study, we examined the effect of such demographic characteristics, as age and gender, on serum PINP level, using the electrochemiluminescence immunoassay ECLIA on the cobas e 411 analyzer. Results. We have detected no significant effect of age on the serum variability of PINP in females (F = 1.453, p = 0.19). However, we observed a significant decrease of PINP level in the female age groups of 40–49 yrs (47.74 ± 21.31, p = 0.02), 60–69 yrs (49.76 ± 25.75, p = 0.03), 70–79 yrs (50.49 ± 26.71, p = 0.04), compared with the age group of 20–29 yrs (58.67 ± 27.46). The regression analysis revealed a significant decrease of PINP level with age in young women and men (20–44 years). When comparing serum PINP level in the oldest age group (80-89 years), we detected its increase in women (55.20 ± 28.38 ng/ml), compared with the 70–79 years group (50.49 ± 26.71 ng/ml), and its decrease in men (54.87 ± 28.24 and 39.16 ± 12.46 ng/ml, respectively). In men, we revealed significant effect of age on the serum variability of PINP (F = 3,077, p = 0.007). Conclusions. The regression analysis showed a significant decrease in PINP level with age in men and women of 20-44 years. In men, we detected a significant effect of age on the variability of serum PINP level. A comparison of serum PINP levels in the oldest age group of 80-89 revealed its increase in women, compared to the 70–79 age group, and decrease in men. The obtained results may be used as reference values for PINP level in serum among representatives of the Ukrainian population of various ages and sexes.